Water and Misconceptions: a review based on chemistry - Sri Winarni; Syahrial Syahrial (Jurnal Ilmiah Wahana Pendidikan, 2020)
Water and the phenomena associated with it are very familiar to students' daily lives. But not a few students experience misconceptions about water. The misconception itself needs to be addressed from the beginning because it has the potential to cause emerged subsequent misconceptions. The initial step to overcome misconceptions can be done by knowing misconceptions that have been reported before. The purpose of this concept study is to map a number of misconceptions and scientific concepts about water that have been reported by previous researchers. Misconceptions and proposition knowledge about water are grouped into three categories namely related to: (1) the nature and changes in physics; (2) atoms and molecules; and (3) intermolecular forces and covalent bonds that occur in water. The most common misconception is "when the water boils and bubbles appear, the bubbles contain oxygen and hydrogen". The most reported knowledge proposition about water is related to the nature and physical changes of substances. Misconceptions about water are interconnected with one another. Besides the existence of knowledge propositions, the teacher needs to know the misconceptions that have happened before. This is useful so that teachers can avoid these misconceptions and convey scientific concepts